2019
DOI: 10.21931/rb/2019.04.02.5
|View full text |Cite
|
Sign up to set email alerts
|

The response of Faba bean (Vicia faba L.) varieties as evaluated by varied plant population densities in the highlands of Arsi Zone, Southeastern Ethiopia

Abstract: Field experiments were carried out in 2016 and 2017 cropping seasons under on-farm conditions in Lemuna Bilbilo District, Southeastern Ethiopia to evaluate the effects of three varieties Degaga, Gora, Moti, and six plant populations (10, 25 (control), 30,50, 70, and 90 plants m-2) on faba bean specific yield and yield components. The experiments were laid out in a randomized complete block design in split plot arrangement in which varieties were assigned to main plots and plant populations to subplots with thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
3
0
4
Order By: Relevance
“…Optimum plant density differs from each variety and location since the different location has different soil type, soil moisture, soil fertility, and relative humidity [46]. In line with these findings, the research conducted on plant densities on faba bean varieties at Lemu-Bilbilo district of Arsi zone, Ethiopia indicated that the highest seed yield of faba bean (4649, 4594, and 4162 kg ha −1 ) was obtained at 90, 70, and 50 plant m −2 for Degaga, Moti and Gora varieties, respectively [47]. The authors also stated that the highest total biomass of 9 t ha −1 was recorded from the highest plant population (90 m −2 ), but did not show significant differences to the total biomass obtained from 70, 50, and 25 (control) plants m −2 .…”
Section: Legumesmentioning
confidence: 79%
“…Optimum plant density differs from each variety and location since the different location has different soil type, soil moisture, soil fertility, and relative humidity [46]. In line with these findings, the research conducted on plant densities on faba bean varieties at Lemu-Bilbilo district of Arsi zone, Ethiopia indicated that the highest seed yield of faba bean (4649, 4594, and 4162 kg ha −1 ) was obtained at 90, 70, and 50 plant m −2 for Degaga, Moti and Gora varieties, respectively [47]. The authors also stated that the highest total biomass of 9 t ha −1 was recorded from the highest plant population (90 m −2 ), but did not show significant differences to the total biomass obtained from 70, 50, and 25 (control) plants m −2 .…”
Section: Legumesmentioning
confidence: 79%
“…En el presente estudio se observó que a un distanciamiento entre plantas de 20 cm hubo más vainas por planta (18.5) (Cuadro 4) pero Dahmardeh et al (2010) La densidad de plantas m -2 tiene un efecto directo sobre el costo de la semilla y el rendimiento final, por lo que es necesario definir la densidad de población óptima para cada variedad y ambiente específico (Dobocha et al, 2019). De acuerdo con los resultados de este estudio lo ideal sería sembrar a 40 o 50 cm entre plantas (31 250 y 25 000 plantas ha -1 ); en la última década el precio de un kilogramo de semilla alcanzó hasta $75.00.…”
Section: Comparación Entre Densidades (D)unclassified
“…El incremento en su rendimiento es relevante para esta región, ya que es una especie estratégica en los sistemas de cultivo de pequeños y medianos agricultores (Díaz et al, 2008), pero esta leguminosa es afectada negativamente por factores climáticos, por fertilidad del suelo y plagas y enfermedades. También depende del suplemento de agua, tipo de variedad y densidad de población, entre otros (Dobocha et al, 2019;Cucci et al, 2019;Mohamed y Rashed, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Majority of the farmers use low yielding of the local varieties which contribute for low production [10,11]. When comparing the yield of fababean in Ethiopia :it is below the world average due to several factors: among these lack of improved seed is a key [12]. Therefore, this activity was aimed at promoting high yielding and most adaptable faba bean varity called " Ashebeka" in the study area by a new extension modality i.e Large Scale Demonstration (LSD) or cluster-based farming with following general and specifi c objectives.…”
Section: Background and Justifi Cationmentioning
confidence: 99%